2016
DOI: 10.1093/neuonc/now150
|View full text |Cite|
|
Sign up to set email alerts
|

Adjuvant chemotherapy and overall survival in adult medulloblastoma

Abstract: Medulloblastoma (MB) is the most common brain tumor in children. However, it is relatively rare in adults, with an estimated incidence of 0.6 per million. 1 The standardof-care management for pediatric MB is postoperative radiotherapy (RT) with craniospinal irradiation (CSI) and posterior fossa or resection bed boost followed by adjuvant chemotherapy. 2,3 Adoption of adjuvant chemotherapy in the pediatric setting has been associated with improved disease control and has allowed successful CSI dose deescalation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 33 publications
1
45
1
1
Order By: Relevance
“…The need of adjuvant chemotherapy is stressed by findings in a recent large retrospective study, where analogous to children, the addition of chemotherapy to radiation conferred a survival benefit. Moreover, they emphasized that 36 Gy CSI with chemotherapy in low‐risk patients failed to exhibit a better prognosis then lower dose of CSI (23–30 Gy) and chemotherapy . As such, young adults with medulloblastoma would benefit from being treated at pediatric centers more specialized in adjuvant chemotherapy.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The need of adjuvant chemotherapy is stressed by findings in a recent large retrospective study, where analogous to children, the addition of chemotherapy to radiation conferred a survival benefit. Moreover, they emphasized that 36 Gy CSI with chemotherapy in low‐risk patients failed to exhibit a better prognosis then lower dose of CSI (23–30 Gy) and chemotherapy . As such, young adults with medulloblastoma would benefit from being treated at pediatric centers more specialized in adjuvant chemotherapy.…”
Section: Epidemiologymentioning
confidence: 99%
“…Moreover, they emphasized that 36 Gy CSI with chemotherapy in lowrisk patients failed to exhibit a better prognosis then lower dose of CSI (23-30 Gy) and chemotherapy. 94 As such, young adults with medulloblastoma would benefit from being treated at pediatric centers more specialized in adjuvant chemotherapy. However, we acknowledge that treatment of young adults in pediatric centers would need to overcome a myriad of complex logistical, bureaucratic, and financial barriers.…”
Section: Medulloblastomamentioning
confidence: 99%
“…Use of adjuvant chemotherapy is generally reserved for adults with high-risk disease, although to date there has not been a consensus reached on regimens, doses, and timing of chemotherapy in pediatric or adult settings. A recent retrospective analysis of large cancer database adding chemotherapy to craniospinal irradiation (CSI) showed an overall survival benefit even in patients with M0 disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly,Postoperative chemotherapy is an important part of the comprehensive treatment of medulloblastoma, and a number of studies have suggested that postoperative chemotherapy can improve the survival of patients with medulloblastoma [18,19]. Research from National Cancer Data Base shown that [19], the 5-year survival rate of the adjuvant chemotherapy group was significantly higher than that of radiotherapy alone, which was 86.1% and 71.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly,Postoperative chemotherapy is an important part of the comprehensive treatment of medulloblastoma, and a number of studies have suggested that postoperative chemotherapy can improve the survival of patients with medulloblastoma [18,19]. Research from National Cancer Data Base shown that [19], the 5-year survival rate of the adjuvant chemotherapy group was significantly higher than that of radiotherapy alone, which was 86.1% and 71.6%, respectively. Recent research suggests that preoperative chemotherapy can also yield survival benefits [20].In terms of the choice of chemotherapy regimen, the combination of three drugs may be more effective [21],lomustine(CCNU), cisplatin, and vincristine or cyclophosphamide, cisplatin, and vincristine are more commonly used.Our study indicated that there was no statistical difference in PFS and OS in the chemotherapy group,the chemotherapy-free group,the EP chemotherapy group and the TMZ chemotherapy group.…”
Section: Discussionmentioning
confidence: 99%